Effects of auriculotherapy in the treatment of nausea and vomiting: a systematic review - Nathaly Bianka Moraes Fróes; Francisca Ariane de Souza Arrais; Priscila de Souza Aquino; Juliana Cunha Maia; Marianne Maia Dutra Balsells (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to identify the effectiveness of auriculotherapy in the treatment of nausea and vomiting through a systematic review of the scientific literature. Methods: it was performed a systematic review of the literature making use of the following data basis: The Scopus, PubMed, CINAHL (Cumulative Index to Nursing and Allied Health Literature), Web of Science, LILACS and Cochrane databases were used. Articles from complete research from randomized controlled clinical trials that describe using auriculotherapy in nausea and vomiting treatment were selected, without restriction of date or language. Results: eleven articles were selected for analysis. The majority approached the population in surgical situations, followed by patients undergoing chemotherapy and pregnant women. As for results, 81% (n=8) of the articles reported that nausea and vomiting were lower in incidence and/or intensity in the intervention group. Conclusions: the review provided relevant data on the effects of auriculotherapy in nausea and vomiting treatment, with a decrease in the intensity and frequency of these symptoms in different populations.